Dental Caries and Associated Factors in 3–5-Year-Old Children in Guizhou Province, China: An Epidemiological Survey (2015–2016) - Guan, Min; Nada, Ola A.; Wu, Juan-juan; Sun, Jiang-ling; Li, Na; Chen, Li-ming; Dai, Tai-ming (Frontiers in Public Health, 2021)
Objective: This study aimed to explore the factors influencing dental caries among 3–5-year-old children in Guizhou Province and the interrelationship between these factors using structural equation modeling, while providing theoretical references to improve the prevention and control strategy. Materials and Methods: A total of 1,291 children aged 3–5 years in Guizhou Province were selected by a multistage stratified and whole group random sampling to examine the caries prevalence in whole-mouth deciduous teeth crowns, and parents were surveyed with questionnaires to analyze the caries-related factors. IBM SPSS Statistics v 23.0 software (IBM, Armonk, NY, USA) was used for statistical analysis. Results: The caries prevalence of children aged 3–5 years in Guizhou Province was 63.1%, the mean decayed-missing-filled teeth was 3.32, the caries filling rate was 0.5%, and there was no statistically significant difference between urban and rural areas and among genders in each age group; results of logistic regression analysis showed that the caries risk increased with the following factors: age, brushing frequency <2 times per day when parents did not take their children to the dentist, and with parents poor evaluation of the oral condition of their children. The higher the education of the parent, the lower the risk of children suffering from caries in deciduous teeth. Conclusions: With an overall poor situation about oral hygiene habits, oral healthcare attitude of the parents, and behavior transformation, the prevalence of dental caries in the deciduous teeth of children aged 3–5 years in Guizhou Province is high, and their caries status was severe, with more than 99% of the caries cases that were untreated. Therefore, prevention and treatment measures of caries in preschool children need strengthening through the improvement of public awareness and the enhancement of the management of oral health habits of their children.